Analisis Perbandingan Metode Peningkatan Wear Resistance - Teguh, Nurdin Hasananto (Jurnal Rekayasa Mesin, 2015)
Improving wear resistance has many variated techniques. The purpose of this work is to compare between DCT (Deep Cryogenic Treated) technique and sand blasting treatment on material steel. XRD ,SEM and TEM are used to examine the changing phase in microstructure level and Hardness contact zones after and before testing. Hence, it can be defined which method that improve significantly the wear resistance.